Special Interest Tourism Activities Planning in Cikawari Waterfall through Risk Analysis and Tourist Interest in Visiting - Wisi Wulandari; Airunisa Dwi Ramadani; Anisa Destya Putri; Haya Khairunnisa; Heydi Rizkiah Shofina; Mochamad Triaji Prasetio (Politeknik Negeri Bandung, 2022)
Every activity at a tourist attraction will have risks. This is no exception for special interest tourism, which has a higher risk than other tourism activities. From the perspective of tourists, they tend to avoid destinations with high potential risks, which also affects their decisions. Cikawari Waterfall is one of the natural tourist attractions in the West Bandung Regency area. Planning for tourism activities at these attractions requires further assessment of the planned provision of special interest activities and facilities (rafting). This study aims to determine the feasibility of the special interest tourism plan by considering the safety risks in tourist attractions and the interest of tourists in visiting. This study uses mixed research methods (qualitative and quantitative) with a purposive sampling technique. This study involved interviews with three key tourism managers and a survey of 118 tourists who visited Cikawari Waterfall. The results showed that tourists consider the risk aspect when visiting. The qualitative and quantitative studies also show that Cikawari Waterfall is considered safe enough against the risk of accidents to visit because there are not many rocks, and the current is not too heavy. The location is easily accessible, so tourists are highly interested in visiting Cikawari Waterfall. In addition, the coordination built in the application of crisis management by the two managers strengthens the position of Cikawari Waterfall to be visited so that tourists do not need to feel anxious when visiting.